Power factor correction of the industrial electrical system during large induction motor starting using ETAP power station. Issue 1 (July 2020) - Mutmainnah,; Fadli Azis, Muhammad; Habibuddin, Julianti
Abstract: This paper presents the power factor correction of the electrical system during the induction motor starting using ETAP power station. There are some problems faced by the electrical system when the motor is started, including voltage drop, high insulation current, and low power factor. The starting motor method used in this paper is starting with VFD. The aim of this research is to improve the power factor during the starting time. The system with a capacitor resulted in a low power factor that lowers the quality of electrical power. By adding capacitor 30 kVAR with each step 0.1 kVAR in the system, the power factor increased to 95.5%.